STUDY OF POTENTIAL ANTITUSSIVE ACTIVITY OF GLYCYRRHIZA GLABRA GRANULES BY USING A COUGH MODEL INDUCED BY SULPHUR DIOXIDE GAS IN MICE - Shitole, Mayuri; Pawar, Vijaykumar (Asian Journal of Pharmaceutical and Clinical Research, 2019)
In respiratory diseases cough is most common symptom. When cough becomes severe, opioids are potent, but they have side effects like sedation, constipation. Therefore, there is a necessary to have effective antitussive formulation, which does not have respiratory depressant activity. The present study was carried out to analysis antitussive activity of Glycyrrhiza glabra L. using a cough model induced by sulphur dioxide gas in experimental mice. The effect of the granules of Glycyrrhiza glabra extract on SO2 gas induced cough in experimental animals have very significant effects at the level of p<0.01 in inhibiting the cough reflex at a dose of 200 mg/kg body weight, in comparison with the control group. Mice were showed an inhibition of 41.17%, in cough on treatment with Glycyrrhiza glabra granules at 60 min experiment. The antitussive activity of the granules was comparable to that of codeine sulphate (10, 15, 20 mg/kg body weight), a standard anti-tussive agent. Codeine sulphate, as a standard drug for suppression of cough, produced 25.29%, 33.33%, 47.13% inhibition in cough at a dose of 10 mg/kg, 15 mg/kg and 20 mg/kg respectively, whereas, codeine sulphate (20 mg/kg) showed maximum 47.13% (p<0.001) inhibition at 60 min of the experiment.